Respuesta :
Answer: x = -5
Step-by-step explanation:
mathpapa.com
Add your equation, then click show work and theres ur work.
Answer:
x=-5
Step-by-step explanation:
Simplifying
4 + -2(x + 7) = 3(x + 5)
Reorder the terms:
4 + -2(7 + x) = 3(x + 5)
4 + (7 * -2 + x * -2) = 3(x + 5)
4 + (-14 + -2x) = 3(x + 5)
Combine like terms: 4 + -14 = -10
-10 + -2x = 3(x + 5)
Reorder the terms:
-10 + -2x = 3(5 + x)
-10 + -2x = (5 * 3 + x * 3)
-10 + -2x = (15 + 3x)
Solving
-10 + -2x = 15 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
-10 + -2x + -3x = 15 + 3x + -3x
Combine like terms: -2x + -3x = -5x
-10 + -5x = 15 + 3x + -3x
Combine like terms: 3x + -3x = 0
-10 + -5x = 15 + 0
-10 + -5x = 15
Add '10' to each side of the equation.
-10 + 10 + -5x = 15 + 10
Combine like terms: -10 + 10 = 0
0 + -5x = 15 + 10
-5x = 15 + 10
Combine like terms: 15 + 10 = 25
-5x = 25
Divide each side by '-5'.
x = -5
Simplifying
x = -5